PROGRAM GEREJA ST. ALBERTUS AGUNG JETIS DAN GEREJA HATI SANTA PERAWAN MARIA TAK TERCELA KUMETIRAN DI KOTA YOGYAKARTA - Agus Mulyono (Harmoni, 2016)
This research found the model of empowerment in“St. Albertus Agung” Jetis Church and “Hati Santa Perawan Maria Tak Bercela” Kumetiran Churchin Yogyakarta shows that the management of both synagogues has been put in a hierarchical structure starting from the Diocese, to the Vicariate (bishop representatives with specific region), and then to the parish by parish priests and his officials. This pattern is a typical of Catholicism, and the same pattern of organization applies also to the parish. The difference is on the way of the organization operates, which depends on the leadership and creativity of the Parish Priest. Meanwhile the economic empowerment of the people to the church is not too visible. The main reason is the economic empowerment of the people is mostly oriented to charity. Whereas, the church facilitates some trainings like trade training to enhance their income. For other programs, the church also provides funds with mortgage payment relief as has been practiced in the parish of Santo Albertus Jetis Yogyakarta. The provision of this fund is caricative in naure. The donation that the two churches receive consists of gwriless and sound systems and some funds for the youth councelling. In the beginning of the year, the church planned to establish pastoral services and they evaluate the program by the end of the year as an overall evaluation for the whole program.